INTERNATIONAL EXPERIENCE ON THE EMPLOYMENT OF PERSONS WITH DISABILITIES - Tkachenko , Olena (Theory and Practice of Public Administration, 2019)
International experience on employment of persons with disabilities is considered. Research and study of international experience will lead to some steps in identifying the right forms and methods, as well as tools to resolve reconciliation between employers and persons with disabilities. The history of the movement of persons with disabilities is the history of the people. Each country already has its own features, timeframes and prerequisites. At the same time, it also has common goals - to improve the situation of people with disabilities, to secure their rights and to integrate them into society. State employment policy in many countries is one of the objectives of addressing discrimination on the basis of disability in the labor market and increasing opportunities for reasonable accommodation in the workplace. The problems of employment of persons with disabilities and social protection of vulnerable sections of the population in Ukraine remain acute, forcing scientists and practitioners to actively seek ways to solve them. In this regard, it is useful for Ukraine to appeal to foreign experience. The reforms initiated in the Ukrainian economy over the last period require modernization and updating of the model of social protection of the population, which is one of the most important problems of formation of Ukrainian society in the conditions of deep market shifts in the national economic system. The negative effects of socio-economic transformation, which occurs without the necessary preventive mechanisms, have led to a sharp decline in the standard of living of the majority of the Ukrainian population. However, the existing system of social protection, created in the Soviet times, no longer meets the requirements of today. On the other hand, the peculiarities of the current socio-economic status of Ukraine do not automatically allow the transfer of certain measures in the field of social protection of the population, which successfully operate in countries with different levels of development of market relations. It should be noted that according to the estimations of international organizations in different spheres of life, Ukraine ranks the first place in the world in terms of child alcoholism, population decline rate, HIV prevalence among adults and pregnant women, the second place in the number of children under 12 years and older, smoking (a quarter of the country’s population, more than Greece only), the third place of the largest number of appeals to the European Court of Human Rights after Russia and Turkey. An alternative proposal should be taken from the proposals submitted in the article, which will combine a quota and anti-discrimination approach. Quotas should be waived in the medium term, but should be accompanied by other incentive measures. The implementation of such model should provide for the implementation of the following strategic social policy objectives, which must be addressed at the state and individual level: ensuring the implementation of approved state programs; implementation, monitoring of social programs at the regional level; control over structural changes in the economy, ensuring livelihoods and maintaining an adequate standard of living for the population; creation of normative base of formation of local budgets; the creation in the regions of the necessary conditions to ensure equal starting opportunities for life, given the minimum social guarantees of the state and the budgetary security of one inhabitant; conducting constant social expert evaluation of the state and development of the region, development of social forecasts and prudent use of them in making management decisions at national and regional level; comprehensive support for entrepreneurship, especially for small and medium-sized businesses; streamlining communal property relations; development of housing and communal services; gradual reform of social infrastructure; providing effective targeted assistance to the most vulnerable sections of the population; active youth policies, support for family, motherhood and childhood and targeted social assistance. The issue of employment of persons with disabilities is a matter of interest not only for States but also for persons with disabilities themselves. Therefore, research and study of international experience will lead to certain steps in identifying the right forms and methods, as well as tools to help reconcile employers and persons with disabilities.